Pengembangan Media Kampanye Sekolah Sehat Berbasis Teknologi pada Siswa Kelas Tinggi Sekolah Dasar - Aulia Rahmawati; Ani Nur Aeni; Ali Ismail (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The health of school-age children is one of the big problems facing Indonesia. School Health Efforts (UKS) aim to improve student health, but UKS is not yet running as optimally as possible. Innovations are needed that can optimize the implementation and achievements of school health, especially in improving student health. This research aims to develop Healthy School Campaign media for high-class students at SDN Gudang Kopi II. This research uses the Research and Development (RnD) method with the ADDIE development model flow. This research was carried out at Gudang Kopi II Elementary School, Sumedang Regency. The type of data collected is qualitative and quantitative data. This research and development produced Healthy School Campaign media in the form of an e-flipbook with product specifications including: 1) Health material and information with 3 main focuses, namely healthy nutrition, physical health, and immunization health, 2) Healthy canteen educational videos, 3) Movement videos and healthy school songs, 4) Application to scan nutritional information from barcodes on food or beverage product packaging, 5) Crossword puzzle games. Based on validation results by experts and student questionnaire responses, this e-flipbook is in the very good category for use as Healthy School Campaign Media.